Applications of noncovariant gauges in the algebraic renormalization procedure (World Scientific, 1998)
The aim of this work is to apply the algebraic renormalization procedure to gauge field models quantized in non-standard gauges. The main ingredient of the algebraic renormalization program is the quantum action principle, which allows one to control in a unique manner the breaking of a symmetry induced by a noninvariant subtraction scheme. In particular, the volume studies the following gauge field models: QED, Yang-Mills theories and topological models (the Chern-Simons and the BF model) in the context of axial-like gauges.